From enfant terrible to problem-solver? Tracing the competing discourse to explain blockchain-related technological diffusion. (October 2021) - Perdana, Arif; Lee, W. Eric; Robb, Alastair
Highlights: Explore how media's reactions reflected technological support/acceptance, neutrality/ambivalence, or resistance. Analyse media sentiments toward blockchain's applications evolved over time. Demonstrate the intricacies of how media shapes and directs the process of technological diffusion. Understanding resistance behavior toward a new technology could help resolve potential issues arising from users' perception of the technology. Abstract: Since the inception of blockchain-related technologies over a decade ago, investors' uptake of the technologies has grown rapidly. But even with the advancement in standing from conceptual beginnings to real-world experimentation, mainstream adoption of the technologies in either organizational or individual contexts has yet to eventuate. To resolve this paradox, we examine progression of the technologies' diffusion instead, and in the process, seek to uncover the underlying dynamics of sentiments at play. Diffusion involves multiple actions by different parties, with social discourses via diverse media playing an essential role. In demonstrating the interplay of support to resistance via media framing and the diffusion of innovation theory, findings from our paper contribute to the technology adoption literature. Understanding resistant behavior toward a new technology area could help resolve potential issues that may arise. This would hopefully lead to better technological implementation outcomes in future.